Yahoo Web Search

  1. Sort by

  1. ...e^(kx) - e^(-kx) ] / [ e^(3x) + e^(-3x) ] When x is large and assume k >= 0 sinh(kx) / cosh(3x) ≈ e^(kx) / e^(3x) = e^(x(k - 3)) For sinh(kx...

    1 Answers · Science & Mathematics · 21/02/2019

  2. k^2 - 3k = 28 k^2 - 3k - 28 = 0 (k - 7)(k + 4) = 0 k = -4, 7 and if you're asked to find x: k = -4: -4 = (x + 3)/(x - 4) -4(x - 4) = x + 3 -4x + 16 = x + 3 16 - 3 = x...

    2 Answers · Science & Mathematics · 18/08/2019

  3. GCD(k,n) = 1 means that k and n have no common divider . Similarly , GCD(n-k,n) = 1 means that n-k and n have no common divider . Assume that n-k and n have a common divider c...

    1 Answers · Science & Mathematics · 26/09/2018

  4. ... SOLUTION: I like to use this notation: C(n, k) = n! / [(n - k)! k!] That would mean: C(n, n - k) = n! / [(n...;--> {A, B, C} So C(n,k) = C(n, n-k)

    6 Answers · Science & Mathematics · 12/09/2019

  5. Replace x with k and y with 2 in x + 2y = 5: k + 2(2) = 5 k = 5 - 4 k = 1

    4 Answers · Science & Mathematics · 25/02/2019

  6. (0.0015/0.03)*10^(m-k) = 5 * 10^7 => (15/300)*10^(m-k) = 5*10^7 => 0.05*10^(m-k) = 5*10^7 => 10^(m-k) = 10^9 => m-k = 9

    4 Answers · Science & Mathematics · 10/02/2019

  7. ... want 1k. So divide both sides of = by 3 33/3 = 3k/3 11 = k Verify LS 4k + 39 4(11) + 39 44 + 39 = 83 RS 7k + 6 7(11...

    6 Answers · Science & Mathematics · 22/11/2018

  8. x^2 - kx + 4 = 0 apply the discriminant formula a = 1 , b = - k, c = 4 b^2 - 4ac = 0 (-k)^2 - 4(1)(4) = 0 k^2 - 16 = 0 k^2 = 16 k = √(16) k = 4 answer// x^2 - 4x + 4 = 0 (x - 2)(x - 2) = 0 x = 2

    8 Answers · Science & Mathematics · 19/05/2019

  9. [k = 1 to n] ∑ (5k)/(3n) ... if you meant something else please confirm. = (5/(3n)) [k = 1 to n] ∑ k = (5/(3n)) n(n+1)/2 = 5(n+1)/6

    1 Answers · Science & Mathematics · 04/05/2019

  10. then f(-2) = 0 or (-2)^4 - k*(-2)^3 + 1 = 0 16 - 8k + 1 = 0 k = -17/8

    2 Answers · Science & Mathematics · 07/06/2019

  1. Try asking your question on Yahoo Answers